Performance analysis of Software Defined Network (SDN) in link failure scenario - Badlishah, Ahmad; Sakari, M.A.I.M; Yaakob, N; Amir, A; Mohd Warip, M.N; Ibrahim, Z. (2019)
The proliferation and advancement in network technologies has brought unprecedented opportunities towards the development of Software Defined Network (SDN) which presents an alternative network architecture that separates data forwarding and control functions to simplify global network management. As SDN is developed to handle largescale network, addressing network dynamics such as link failure remains challenging. Link failure in SDN could still cause major performance disruption which can lead to severe performance degradation for underlying applications. Therefore, this paper analyses several link failure circumstances in SDN and show how it reacts to such situations. As SDN decouples data and control planes, routing algorithm is determined by its controller. In this paper, routing algorithm is used to control the behaviour of the network traffic when one or more links are disconnected. Ryu controller which is one of the open controllers in SDN, acts as a brain to adapt how traffic is controlled for the whole network. Performance of SDN in different network topologies is compared in terms of throughput and Round-TripTime (RTT) which shows desirable SDN performance